The influence of the SEAFDEC-Leganes research station on the socio-economic life of the community as perceived by the residents of Barangay Nabitasan, Leganes, Iloilo. - Espano, Ma. Celia Jinon
The SEAFDEC, an international research institution, was primarily created in response to the need to modernize and upgrade the fisheries industry and contribute to the solution of the global economic problem. One of its research stations is located in Leganes, which is complementary with the other two (2) stations located in Tigbauan, and Binangonan, Rizal. , The SEAFDEC-Leganes Research Station has been in operation for the last twelve years, but no study has been conducted to find out the influence of this Station to the community where it is located. In this light, this study has the following objectives: a)To find out the rationale of the establishment of the SEAFDEC-Leganes Research Station (LRS) in Barangay Nabitasan, Leganes, its growth and expansion as well as its role/functions to the improvement of the aquaculture industry in the said community; b)To assess the socio-demographic profile of the community, and; c)To determine the influence of the SEAFDEC-LRS on the socio-economic life as perceived by the community and particularly to the fishpond operators/caretakers. This focus of the study is primarily limited to the above mentioned objectives. The study was conducted in Barangay Nabitasan, Leganes, where the SEAFDEC-LRS presently stands. There were three types of respondents: the residents of the barangay, the SEAFDEC-LRS personnel and some municipal officials. The community respondents were either husbands or wives of the household taken from a random sample (50) of the 220 households of the five sitios of the community. Some SEAFDEC personnel and municipal officials who are knowledgeable of the establishment of the LRS were interviewed to give more information on the rationale and roles of the LRS. Prior to the final data collection, a pre-test was conducted to check the validity of the interview schedule constructed. The researcher also made use of the municipal documents (i.e. resolutions, municipal development plans). Simple frequency counts, rankings, percentages and averages were used to analyze the socio-demographic profile of the respondents and influence of the LRS as perceived by the respondents. The reactions of the residents towards the LRS was analyzed by the use of a Four-Point scale method of analysis. The major results of the study were based from the stated objectives. They are presented in the following statements. The major factor why Leganes was chosen as the Brackishwater Aquaculture Research Station of the SEAFDEC is because of the fact that the municipality, specifically Barangay Nabitasan, has sufficient natural resources (i.e., almost seven hundred hectares of fishponds necessary for fish research). Secondly, the salinity of the water is appropriate for brackishwater aquaculture industry. The LRS offers extension and training opportunities to the general population through symposia, seminars, on-site demonstrations and publications. Since its humble start in 1973, it had grown into a major research facility sharing technical gains brackishwater aquaculture which earned for the SEAFDEC Aquaculture Department international stature as an international research institution. Through these achievements, the LRS is included in the world map of aquaculture and has made the community a tour site for foreigners and guests coming to the Municipality. The SEAFDEC-LRSA also provides labor intensive opportunities for the residents of Barangay Nabitasan. The establishment of the said Station extends financial assistance to the municipality of Leganes through payment of annual lease from the municipality-owned fishponds. The area has a pronounced dry season from February to April. It is wet during the rest of the year. The Station's water supply serves the residents especially during the summer months. (p)In relation to the socio-demographic profile of the community, the youngest respondents was 18 years old, while the oldest was 66 years old. The average age of the respondents was 42 years old, while the average number of children per family was 6. Majority of the respondents were elementary graduates. In relation to the labor force of the community, majority of the total household members included in the study who are gainfully employed are the husbands. Majority of them are laborers working in the fishponds on a daily basis. (p)Less than 2/3 of the respondents have stayed in the community since birth and they have not gone out of the community seeking for jobs. The main reason is the fact that there is an abundance of work and/ or means of livelihood in the surrounding areas. Majority of them are contented with their community life because earning a living is not a problem and they claimed that the LRS had improved their socio-economic life and rated the establishment of the LRS as satisfactory. The aspirational level of the respondents can be concluded as to have increased because majority of them would want their children to be permanently employed as administrative and technical employees, researchers, and other high ranking positions in the SEAFDEC-LRS through the acquisition of college education. (p)According to the respondents, the presence of the said station primarily improved their social conditions. (p)It beautifies the community and provides potable drinking water facilities. It extends modern technological know-how to the fishpond operations, as well as ensures the availability of alternative employment. (p)The research data revealed that there is a slight change in the production output in terms of the annual production income of the fishpond operators from P11,750.00 to P19,250.00. In general, the respondents' reaction towards the establishment of the LRS is favorable because of: a)LRS helped the socio-economic condition of the community; b)the lifestyle of the residents was changed for the better, and; c)the LRS provides labor-intensive opportunities.